The Regularities of Nitrogen Diffusion during the Ion-Beam Nitriding Process of Austenitic Thermal-Sprayed Coating - Aleksandr N. Grigorchik; Vladimir A. Kukareko; Aleksey V. Byeli; Marat A. Belotserkovsky; Boris B. Khina (Механика машин, механизмов и материалов, 2016)
The distribution of nitrogen and chromium atoms in nearsurface layers of austenitic thermal sprayed coating subjected to ionbeam nitriding at 870 K has been studied. It is established that the sprayed particles of the coating possess various chromium content. It is shown that, as a result of ionbeam nitriding, the nitrided layers have a higher depth in particles with a lower chromium concentration. The estimation of diffusion coefficient of nitrogen in the sprayed particles with different chromium content has been performed. It is shown that the diffusion coefficient of nitrogen during ionbeam treatment significantly exceeds the values observed during the process of traditional gasphase nitriding. It is established that the diffusion coefficient of nitrogen tends to decrease with increasing chromium content in the sprayed particles of the coating and decreases with distance from the outer surface.